The effectivenesss of ethyl formate to control beetles of stored milled rice and relationship to eating qualities of rice / Nur Amira Hamid - Hamid, Nur Amira (2016)
Ethyl formate was tested both in laboratory and in polyvinyl chloride tent fumigation for disinfesting milled rice to control Sitophilus oryzae, Tribolium casteneum, Oryzaephilus surinemensis and Rhyzopertha dominica. The laboratory experiments were to verify the effective gas exposure time and the lethal concentration to kill 99% of the population (LC99). Milled rice fumigation in 1-tonne polyethylene bags with test insects was to assess procedure for field application for bagged rice during storage, the effective concentration, exposure time, and effect on eating quality of the cooked rice. The LC99 and the calculated Ct product from laboratory studies conducted in desiccators for Tribolium casteneum was respectively 50.72 mgL'1 , 239.00 mghL"1 ; Oryzaephilus surinemensis 26.22 mgL"1 , 158.5 mghL"1 ; Sitophilus oryzae 50.22 mgL' , 239 mghL"1 ; and Rhyzophertha dominica 26.83 mgL"1 , 83.94 mghL"1 . Based on least susceptible Tribolium casteneum, milled rice fumigation requires 291.9 gm"3 to achieve LC99 and Ct product 162.5 ghm"1 after 24 hour; 227.6 gm"3 and 562.0ghm"3 for 48 hour. It is recommended 230-300 gm"3 concentration range and 48 hour exposure period be adopted to ensure effectiveness against all species and insect stages in milled rice fumigation. The eating quality of cooked rice in terms of the aroma, stickiness, taste, colour and overall acceptability was not affected from the multiple exposure (3 times) to the ethyl formate. Findings from this study indicated ethyl formate is a potential replacement for methyl bromide and phosphine but it is recommended that the compressed fumigant with carbon dioxide can be used for commercial application to improve evaporation and gas penetration within fumigated space of the liquid formulation used in this study.